2021
DOI: 10.1002/ejsp.2744
|View full text |Cite
|
Sign up to set email alerts
|

Tethered humanity: Humanizing self and others in response to interpersonal harm

Abstract: We propose an integrative framework in which the self‐image of perpetrators and victims in interpersonal conflictual relationships becomes tethered to each other. To the extent that both parties stop seeing themselves as fully human when interpersonal harm is inflicted, we theorize that this state motivates attempts at restoration. Specifically, we propose the tethered humanity hypothesis which ascertains that perpetrators or victims can reclaim their full human status by re‐establishing the humanness of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 59 publications
3
19
0
Order By: Relevance
“…Similar to the current study, Borinca et al (2021 , Study 3) investigated the effect of the perpetrator group’s apology on the improvement of intergroup relations through the victims’ perception of humanness, and Vaes and Bastian (2021 , Study 3) investigated whether accepting an apology or not affects dehumanization toward the perpetrator. However, Borinca and colleagues only focused on the position of the victim group members and did not verify the impact of intergroup apology on specific dimensions of humanness, and Vaes and Bastian primarily focused on interpersonal rather than intergroup conflict.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar to the current study, Borinca et al (2021 , Study 3) investigated the effect of the perpetrator group’s apology on the improvement of intergroup relations through the victims’ perception of humanness, and Vaes and Bastian (2021 , Study 3) investigated whether accepting an apology or not affects dehumanization toward the perpetrator. However, Borinca and colleagues only focused on the position of the victim group members and did not verify the impact of intergroup apology on specific dimensions of humanness, and Vaes and Bastian primarily focused on interpersonal rather than intergroup conflict.…”
Section: Introductionmentioning
confidence: 93%
“… Borinca et al (2021 , Study 3) demonstrated that an apology offered by the perpetrator group (i.e., Serbians) reduced victims’ (i.e., Albanians) dehumanization of them more than when the apology was refused by the perpetrator group, and then, such lessened dehumanization facilitated the victims’ willingness to intergroup contact and reconciliation. In a study by Vaes and Bastian (2021 , Study 4), a victim who suffered social exclusion exhibited less dehumanization and more intention to forgive the perpetrator when they received an apology than when they did not receive it from the perpetrator. According to Leidner et al (2013 , Study 1), if the victims receive apologies from the perpetrators, they would be more likely to reappraise the perceived sentience of the perpetrators and to perceive their HN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we leveraged the rich media content at our fingertips by searching open-access online repositories (e.g., YouTube, Vimeo) for videos that humanized Russian soldiers. We identified six videos we believed would humanize Russian soldiers by individuating them 54,63,64 , highlighting their moral agency through their opposition to the invasion 42,65,66 , and revealing their remorse for their participation in it 53,67,68 .…”
Section: Studymentioning
confidence: 99%
“…Such immoral offenses have psychological and relational consequences (Baumeister et al, 1990), but have also shown to lead to changes in the way we perceive ourselves and the perpetrators in human terms (Bastian & Haslam, 2010, 2011). Recent theoretical advances have introduced the tethered humanity hypothesis (Vaes & Bastian, 2021) that allows us to make predictions about the way self and other humanness judgments change and are interconnected in response to interpersonal harm. While previous research has shown how both perpetrators and victims self-dehumanize when they commit or suffer immoral treatment (Bastian & Haslam, 2010; Bastian et al, 2012, 2013, 2014), the tethered humanity hypothesis states that the humanity of the perpetrator or the victim can get caught up in the humanity of the opposing party when attempts at reconciliation are undertaken and accepted, resulting in the rehumanization of both parties involved.…”
mentioning
confidence: 99%